Transforming Qardh from a Cost Center to an Investment Enabler: A Tiered Financing Model Based on Wa’ad Mulzim - Adi Rosadi; Ramdani Wahyu Sururie (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
Qardh financing in Islamic financial institutions in Indonesia faces a dilemma between its social function and the need for financial sustainability. The absence of a mechanism that allows institutions to obtain commercial certainty causes Qardh to remain a cost center that is not developed institutionally. The study offers a Tiered Financing model that expressly separates the two layers of Qardh financing as a social portfolio and Mudharabah as a commercial portfolio through contractual and temporal separation. The two are connected by Waʿad Mulzim, which serves as an instrument of bilateral commitment to reduce the risk of customer leakage while maintaining compliance with the prohibition of ta’alluq al-’uqud. A conceptual analysis of the structure of contracts, sharia standards, and regulatory implications shows that this tiered architecture provides a framework that can bridge the social and commercial goals of the institution in a balanced manner. This model also offers a theoretical contribution in the form of the integration of risk-governance mechanisms in the tabarru’ contract to improve institutional sustainability. The findings of this study suggest that Tiered Financing is a viable alternative to strengthen Qardh 's role in modern Islamic finance, while remaining within the corridor of core sharia principles.